1979
DOI: 10.1111/j.1532-5415.1979.tb01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Male and Female Climacteric*

Abstract: The gonadal steroids--estrogens and androgens--appear to have a mood-elevating, psychotonic effect. The improved sense of well-being and increased vigor probably is engendered by restoration of somatic efficiency and psychic equilibrium. 1. The male climacteric, as observed in a limited number of men, is associated with a low level of serum testosterone. The levels of follicle-stimulating hormone and luteinizing hormone are not elevated because estrogen concentration continues unaltered well into old age. Andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, more intense nuclear ERα labeling was found in the SCN neurons of women as compared with the SCN neurons of male subjects, which is an opposite sexually dimorphic tendency to that found previously for nuclear androgen receptor immunoreactivity in SCN neurons (table 3) [40]. The fact that men in general do not suffer that much from ‘andropausal’ disturbances is generally explained by the fact that testosterone levels in men do not decrease as strongly as estrogen levels in menopausal women, although hot flushes, insomnia and mood disturbances (irritability, anxiety, depression) can be manifestations of the male climacteric as well [for reviews see, 46, 47, 48]. There are indeed human data which indicate that sex hormones have effects on mood [18, 22, 48, 49], sleep [19, 20]and heat balance [21, 50].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, more intense nuclear ERα labeling was found in the SCN neurons of women as compared with the SCN neurons of male subjects, which is an opposite sexually dimorphic tendency to that found previously for nuclear androgen receptor immunoreactivity in SCN neurons (table 3) [40]. The fact that men in general do not suffer that much from ‘andropausal’ disturbances is generally explained by the fact that testosterone levels in men do not decrease as strongly as estrogen levels in menopausal women, although hot flushes, insomnia and mood disturbances (irritability, anxiety, depression) can be manifestations of the male climacteric as well [for reviews see, 46, 47, 48]. There are indeed human data which indicate that sex hormones have effects on mood [18, 22, 48, 49], sleep [19, 20]and heat balance [21, 50].…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, the estrogens have not been definitively studied in males. Most investigators have reported that estrone (Ei) and estradiol (E 2 ) levels remain constant or increase slightly with age (2,4,8,19,(31)(32)(33).…”
mentioning
confidence: 99%
“…Despite the fact that many men with low testosterone levels are asymptomatic [25], many others have a partial, gradual, and variable decline in T associated with various clinical symptoms, described as a syndrome called partial androgen deficiency of the aging male (PADAM) [26]. PADAM is characterized by sexual, somatic, and behavioral symptoms, with insidious onset and slow progression [27]: diminished sexual desire and erectile quality, particularly nocturnal erections [28,29]; decrease in lean body mass, with associated diminution in muscle volume and strength; increase in visceral fat [30][31][32], decrease in bone mineral density, resulting in osteoporosis [33]; reduction in body hair and skin alterations [34]; weakness, fatigue, depression, lack of motivation and energy, lower psychological vitality, anxiety, irritability, insomnia, decreased work and sport performances; difficulty in concentrating, memory impairment, and low dominance [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%